Study of the effect of the herbal composition SR2004 on hemoglobin A1c, fasting blood glucose, and lipids in patients with type 2 diabetes mellitus - Sumit Chatterji; Dov Fogel (Integrative Medicine Research)
Background: Type 2 diabetes mellitus (T2DM) is a metabolic disorder characterized by raised blood glucose levels and peripheral insulin resistance. It is an increasingly prevalent global healthcare concern. Conventional treatment options are limited and in this context, there is renewed interest in evaluating the clinical and biological effects of traditional therapies. We assess the effect of a new herbal composition SR2004 on the hemoglobin A1c (HbA1c), fasting blood glucose, and lipid profiles of patients with T2DM. Methods: This is a single center, unblinded, prospective interventional study conducted in Israel. The composition SR2004 includes Morus alba, Artemisia dracunculus, Urtica dioica, Cinnamomum zeylanicum, and Taraxacum officinale. One hundred and nineteen patients with diagnosed T2DM were enrolled and received SR2004 in addition to their usual medications. HbA1c, fasting blood glucose, and lipid profiles at 12 weeks were compared with baseline. In addition, the tolerability and side effects of SR2004 were recorded. Results: One hundred and three patients completed 12 weeks of follow-up (87%) and were included in the results. At 12 weeks, HbA1c reduced from 9.0% to 7.1% (22%; p < 0.0001), mean blood glucose decreased from 211 mg/dL to 133 mg/dL (37% reduction; p < 0.0001), mean total cholesterol to 185 mg/dL (13% reduction; p < 0.01) and mean serum triglycerides to160 mg/dL (a reduction of 40% from baseline; p < 0.001). Twelve patients (12%) had no response with SR2004 supplementation. In addition, of thirteen patients who took insulin at baseline, five required only oral hypoglycemics and another five reduced their daily insulin requirements by 30% at 12 weeks. Clinical observations included improvements in vasculopathy, including reversal of established retinopathic changes in two patients.No major adverse effects were observed, with minor abdominal symptoms reported in sixteen patients (16%). Conclusion: SR2004 supplementation significantly reduced HbA1c, blood glucose, and lipids with good tolerability and no observed adverse interactions with conventional medications. Some interesting findings relating to the reversal of microvascular phenomena warrant further research to elucidate the mechanisms of action of this novel composition. Keywords: Glucose, Herbal, Lipids, Retinopathy, Type 2 diabetes mellitus